The Author’s Relationship with the Addressee as a projection of the lecturer–student relationship in Stasys Šalkauskis’ Textbook “The Basics of General Scientific Work Methodology” - Rutkienė, Lina; Vladarskienė, Rasuolė (Pedagogika, 2025)
The article examines the peculiarities of the expression of the relationship between the author and the addressee in one of the first Lithuanian academic methodology textbooks – Stasys Šalkauskis’ book “The Basics of General Scientific Work Methodology”. The expression of the relationship between the textbook’s author and the addressee is shaped stylistic, postillogical, and genre-specific features, all of which are oriented toward the primary goal – to teach the addressee. The relationship created between the author and the addressee in the textbook is associated with Šalkauskis’ pedagogical views – his perspective on the teacher and the student, and their connection. In the textbook, Šalkauskis, as the author, positions himself to be visible – not only as a monologic narrator but also as a creator and developer of dialogue. The author’s persona in the textbook is revealed through a grammatical person, expressed either by verb endings, the personal pronoun “I” in forms like man (me), or the first-person plural – we, which encompasses different hierarchical levels. The relationship between the author and the addressee in the textbook is developed using interpersonal metadiscourse markers. Although the knowledge levels of the author and the addressee differ, the author treats the addressee with great respect: either by identifying with them, by expressing directives through impersonal forms without directly naming the addressee, or by referring to the addressee using nominative forms of specific nouns, avoiding vocative constructions altogether.